Epidemiological profile of cocaine users on treatment in psychiatrics hospitals, Brazil - Ferreira Filho, Olavo Franco (2003)
OBJECTIVE: To describe the epidemiological profile and patterns of cocaine use among hospitalized drug users. METHODS: A cross-sectional study was carried out among drug users, aged 18 years or more, hospitalized in one out six selected psychiatric hospitals in the metropolitan area of Greater São Paulo, whose clinical conditions allowed them to reliably answer to a standardized questionnaire and who agreed to participate. Six psychiatric hospitals who attended spontaneously referred public and private patients from all Greater São Paulo were selected. Data collection was conducted using structured interviews, individually applied by a trained psychologist. Statistical analysis was performed using Student t-test and Chi-square test at p